Effect of Graphene and Carbon Nanotube on Low-Density Polyethylene Nanocomposites - Sabet, M. (2019)
The nanocomposites of low-density polyethylene contain graphene (LDPE/Gr) and low-density polyethylene contains carbon-nanotubes (LDPE/CNTs) with different Gr loadings (0.5, 1, and 3 wt) were formulated with a melt-mixing method. The distribution of Grs in LDPE was detected by scanning electron microscopy. In this study, morphological, electrical, thermal, tensile, and rheological properties of nanocomposites were comparatively investigated. The outcomes were reviewed and it was recognized that LDPE/Gr nanocomposites reveal superior properties than LDPE/CNTs nanocomposites at the same loadings. The superior performance of LDPE/Gr nanocomposites attributes to the large aspect ratio of Gr and its two dimensional flat surfaces which effect in increasing physical interlinking with LDPE chains and expanded the interface zone at fillerâLDPE interface. It was also identified that the achieved results for LDPE/CNT nanocomposites, which has a compact surface area and linkage with LDPE, are less noticeable than similar Gr compounds due to higher interfacial interactions between Gr and LDPE. The thermomechanical results of LDPE/Gr nanocomposites have been studied and the influence of nanoscaled strengthening in the thermoplastic matrix has been investigated. The existence of Gr limits the flexibility of LDPE chains, increases the rigidity and the strength of the LDPE-nanocomposites. This study compares how a flat or roll structure of carbon nano-structure additive (Grs vs. CNTs) can change the various properties of LDPE nanocomposites. J. VINYL ADDIT. TECHNOL., 25:35â40, 2019. Â© 2018 Society of Plastics Engineers. Â© 2018 Society of Plastics Engineers